Quorum Sensing Inhibiting Activity of Cefoperazone and Its Metallic Derivatives on Pseudomonas aeruginosa - Naga, Nourhan G.; El-Badan, Dalia E.; Rateb, Heba S.; Ghanem, Khaled M.; Shaaban, Mona I. (Frontiers in Cellular and Infection Microbiology, 2021)
The last decade has witnessed a massive increase in the rate of mortalities caused by multidrug-resistant Pseudomonas aeruginosa. Therefore, developing new strategies to control virulence factors and pathogenicity has received much attention. One of these strategies is quorum sensing inhibition (QSI) which was developed to control Pseudomonas infection. This study aims to validate the effect of one of the most used β-lactam antibiotics; cefoperazone (CFP) and its metallic-derivatives on quorum sensing (QS) and virulence factors of P. aeruginosa. Assessment of quorum sensing inhibitory activity of CFP, cefoperazone Iron complex (CFPF) and cefoperazone Cobalt complex (CFPC) was performed by using reporter strain Chromobacterium violaceum ATCC 12472. Minimal inhibitory concentration (MIC) was carried out by the microbroth dilution method. The influence of sub-MICs (1/4 and 1/2 MICs) of CFP, CFPF and CFPC on virulence factors of P. aeruginosa was evaluated. Data was confirmed on the molecular level by RT-PCR. Also, molecular docking analysis was conducted to figure out the possible mechanisms of QSI. CFP, CFPF, and CFPC inhibited violacein pigment production of C. violaceum ATCC 12472. Sub-MICs of CFP (128- 256 μg/mL), and significantly low concentrations of CFPC (0.5- 16 μg/mL) and CFPF (0.5- 64 μg/mL) reduced the production of QS related virulence factors such as pyocyanin, protease, hemolysin and eliminated biofilm assembly by P. aeruginosa standard strains PAO1 and PA14, and P. aeruginosa clinical isolates Ps1, Ps2, and Ps3, without affecting bacterial viability. In addition, CFP, CFPF, and CFPC significantly reduced the expression of lasI and rhlI genes. The molecular docking analysis elucidated that the QS inhibitory effect was possibly caused by the interaction with QS receptors. Both CFPF and CFPC interacted strongly with LasI, LasR and PqsR receptors with a much high ICM scores compared to CFP that could be the cause of elimination of natural ligand binding. Therefore, CFPC and CFPF are potent inhibitors of quorum sensing signaling and virulence factors of P. aeruginosa.